Anti-fracture high-strength belt special for range hood and preparation method of anti-fracture high-strength belt

By mixing high-density polyethylene and silicon-containing flame-retardant polyurethane and adding materials such as compatibility agents to prepare a special belt for hoods with high strength with cracks, the existing belts are solved, and the problems of serious adhesive materials and poor wear resistance during use are achieved, achieving high strength, low friction and wear resistance.

CN119798825AActive Publication Date: 2025-04-11GUANGZHOU HAOYU ELECTROMECHANICAL EQUIP CO LTD

Patent Information

Application Number
CN202510095392.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

During the use of the conveying belts in the existing tobacco industry, there are problems such as serious adhesive materials, poor wear resistance, and large friction coefficient, resulting in poor product taste and easy equipment damage.

Method used

High-density polyethylene and silicon-containing flame-retardant polyurethane are used as the main materials, and compatibility agents, carbon nanotubes, light calcium carbonate and anti-aging agents are added. Through melting stirring and cross-linking reactions, a special belt for hoods with high strength resistance to fracture is prepared.

Benefits of technology

The belt is achieved with high strength, fracture resistance and low friction coefficient, which improves the wear resistance and flame retardant performance of the product, extends the service life of the equipment and improves the taste of tobacco products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of transportation equipment, in particular to an anti-fracture high-strength belt special for a range hood and a preparation method of the anti-fracture high-strength belt. The preparation method comprises the following steps: grafting low-density polyethylene with acrylic acid, and reacting with a polyurethane prepolymer to prepare a compatilizer; then, 3-amino-1, 2, 4-triazole, hydroxycitronellal and 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are subjected to a reaction, and a flame retardant is prepared; and reacting the polyurethane prepolymer with dihydroxyl-terminated polydimethylsiloxane, adding a flame retardant for terminating after chain extension, and curing to obtain the silicon-containing flame-retardant polyurethane. The preparation method comprises the following steps: mixing high-density polyethylene and silicon-containing flame-retardant polyurethane, adding a compatilizer, carbon nanotubes, light calcium carbonate and an anti-aging agent, melting and stirring, cooling, adding dicumyl peroxide, carrying out a cross-linking reaction, and carrying out injection molding, demolding, cutting, cutting, edge sealing and polishing to obtain a finished product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of transportation equipment, and in particular to a high-strength, break-resistant belt specially designed for range hoods and a preparation method thereof. Background Art

[0002] In the process of tobacco preparation, tobacco leaves, tobacco shreds, tobacco stems and other materials need to be processed separately, which often involves the transportation of materials. Tobacco leaves themselves have complex ingredients, which contain complex compound components, and different formulas of flavors and spices are added during production. Therefore, impurities often remain on the surface of the belt, resulting in a poor taste of tobacco products.

[0003] The existing conveyor belts in the tobacco industry are generally polyvinyl chloride belts, polyethylene belts, and thermoplastic polyurethane elastomer belts. Among them, polyvinyl chloride belts have high surface energy and are seriously sticky; polyethylene belts have low surface hardness, poor wear resistance, and large film porosity, which makes it easy for oil stains to penetrate over time; while thermoplastic polyurethane elastomer belts have high mechanical strength and high wear resistance, but a large friction coefficient. Based on the above technical problems and the characteristics of different materials, it is necessary to develop a high-strength, anti-fracture special belt for tobacco machines. Summary of the invention

[0004] The object of the present invention is to provide a high-strength, break-resistant belt specially used for range hoods and a method for preparing the same, so as to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-strength belt for range hoods that is resistant to breakage and a preparation method thereof, comprising the following steps: High-density polyethylene and silicon-containing flame-retardant polyurethane are mixed to obtain a mixed material; the mixed material, a compatibilizer, carbon nanotubes, light calcium carbonate, and an antioxidant are melted and stirred at 200-230° C., the temperature is lowered to 110-120° C., dicumyl peroxide is added for cross-linking reaction for 120-130 seconds, and a finished product is obtained through injection molding, demolding, trimming, cutting, edge sealing, and polishing.

[0006] Furthermore, in the mixed material, the content of each component, by weight, is 85-90% high-density polyethylene and 10-15% silicon-containing flame-retardant polyurethane.

[0007] Furthermore, the amount of each component, by weight, is 100 parts of the mixed material, 8 to 12 parts of the compatibilizer, 5 to 9 parts of the carbon nanotubes, 3 to 5 parts of light calcium carbonate, and 2 to 3 parts of the antioxidant.

[0008] Furthermore, the preparation method of the compatibilizer comprises the following steps: Step 1: Toluene diisocyanate and polypropylene glycol 1000 are mixed, dibutyltin dilaurate as a catalyst is added, and the mixture is stirred and reacted at 75-90°C under nitrogen protection to obtain a polyurethane prepolymer; Step 2: Mix low-density polyethylene and xylene, heat until the polyethylene is dissolved, add acrylic acid and benzoyl peroxide to react, pour the product into anhydrous ethanol, filter out the mother liquor, soak the precipitate in anhydrous ethanol for washing, and vacuum dry to obtain polyethylene grafted with acrylic acid; Step 3: The polyethylene grafted acrylic acid and the polyurethane prepolymer are mixed, and the temperature is raised to 90-100°C under the protection of a nitrogen environment. After reacting for 10-12 hours, the temperature is lowered to 60-70°C, and the unreacted isocyanate groups are capped with anhydrous ethanol. The ungrafted polyurethane prepolymer in the reactant is removed with N,N-dimethylformamide, and vacuum dried to obtain a compatibilizer.

[0009] Further, in step 1, toluene diisocyanate and polypropylene glycol 1000 are reacted in a molar ratio of 2:1.

[0010] Furthermore, in step 2, the weight ratio of benzoyl peroxide, acrylic acid and polyethylene is (0.5~0.8):(12~15):100.

[0011] Furthermore, in step 3, the mass ratio of polyethylene grafted acrylic acid to polyurethane prepolymer is 100:(8~10).

[0012] Furthermore, the preparation method of the silicon-containing flame-retardant polyurethane comprises the following steps: S1: Toluene diisocyanate and polypropylene glycol 1000 are mixed, dibutyltin dilaurate as a catalyst is added, and the mixture is stirred and reacted at 75-90° C. under nitrogen protection to obtain a polyurethane prepolymer; S2: Disperse 3-amino-1,2,4-triazole and hydroxycitronellal in anhydrous ethanol, heat and reflux for 8-10 hours, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and continue to reflux for 8-9 hours, cool naturally after the reaction is completed, wash the precipitate with anhydrous ethanol by centrifugation, and vacuum dry to obtain a flame retardant; S3: 100 parts of polyurethane prepolymer and 10-15 parts of dihydroxy-terminated polydimethylsiloxane are mixed, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 70-90°C under nitrogen protection, the temperature is kept for reaction for 2-3 hours, 1,4-butanediol is added, and the chain extension reaction is performed for 1-2 hours; flame retardant is continued to be added, the end-capping reaction is performed for 0.5-1 hour, and the silicon-containing flame-retardant polyurethane is obtained by aging.

[0013] Furthermore, in S1, toluene diisocyanate and polypropylene glycol 1000 are reacted in a molar ratio of 2:1; in S2, the molar ratio of 3-amino-1,2,4-triazole, hydroxycitronellal, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1:1; in S3, the amount of each component, by weight, is 100 parts of polyurethane prepolymer, 10-15 parts of dihydroxy-terminated polydimethylsiloxane, 2-3 parts of 1,4-butanediol, and 8-10 parts of flame retardant.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention provides a method for preparing a high-strength belt for a special range hood that is resistant to fracture, comprising mixing high-density polyethylene and silicon-containing flame-retardant polyurethane, adding a compatibilizer, carbon nanotubes, light calcium carbonate, and an antioxidant, melting and stirring, cooling, adding dicumyl peroxide for cross-linking reaction, and then performing injection molding, demolding, trimming, cutting, edge sealing, and polishing to obtain a finished product. By blending a polyethylene material with a low friction coefficient with a polyurethane material with a high tensile strength, a composite material with good performance is obtained, which can be used to prepare a high-strength belt for a special range hood that is resistant to fracture.

[0015] Among them, the compatibilizer is obtained by first grafting acrylic acid on low-density polyethylene, and then reacting the carboxyl group with the isocyanate group on the polyurethane prepolymer. The addition of the compatibilizer improves the compatibility between polyethylene and silicon-containing flame-retardant polyurethane, so that polyethylene and silicon-containing flame-retardant polyurethane produce cross-linking, thereby forming a network structure, which can prevent small-molecule inorganic materials from migrating to the surface of the material. When preparing silicon-containing flame-retardant polyurethane, the polyurethane is first capped with a flame retardant with a terminal hydroxyl group prepared from 3-amino-1,2,4-triazole, hydroxycitronellal, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and at the same time, an organosilicon segment is introduced into the polyurethane. On the one hand, organosilicon can produce a synergistic effect with the flame retardant to improve the flame retardant performance; on the other hand, organosilicon can improve the toughness of the material and prevent it from breaking due to external force during use.

[0016] In addition, it should be noted that when the content of silicon-containing flame-retardant polyurethane is too high, the compatibility of the blending system deteriorates, thereby affecting the performance of the product. Therefore, by weight, the belt prepared by mixing 85-90% high-density polyethylene and 10-15% silicon-containing flame-retardant polyurethane has the best performance. DETAILED DESCRIPTION

[0017] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0018] Materials and sources used in the present invention: low-density polyethylene comes from Shanghai Petrochemical, model LF5600; high-density polyethylene comes from Dushanzi Petrochemical, model DMDA-8008; dihydroxy-terminated polydimethylsiloxane (Mn=1000) comes from Shanghai Tiger Polymer Technology Co., Ltd.; the average particle size of light calcium carbonate is 0.01~0.1μm; the average tube diameter of carbon nanotubes is 10~25nm; the antioxidant is antioxidant 4020.

[0019] Embodiment 1: A high-strength belt for a range hood that is resistant to fracture and a method for preparing the same, comprising the following steps: Step 1: Toluene diisocyanate and polypropylene glycol 1000 are mixed, a catalyst dibutyltin dilaurate is added, and the mixture is stirred and reacted at 75° C. under nitrogen protection to obtain a polyurethane prepolymer; wherein the toluene diisocyanate and polypropylene glycol 1000 are reacted in a molar ratio of 2:1; Step 2: S21: mixing low-density polyethylene and xylene, heating until the polyethylene is dissolved, adding acrylic acid and benzoyl peroxide to react, pouring the product into anhydrous ethanol, filtering out the mother liquor, soaking the precipitate in anhydrous ethanol for washing, and vacuum drying to obtain polyethylene grafted with acrylic acid; wherein the weight ratio of benzoyl peroxide, acrylic acid and polyethylene is 0.5:15:100; S22: polyethylene grafted acrylic acid and polyurethane prepolymer are mixed, heated to 90°C under nitrogen environment, reacted for 10 hours, cooled to 60°C, unreacted isocyanate groups are capped with anhydrous ethanol, ungrafted polyurethane prepolymer in the reactants is removed with N,N-dimethylformamide, and vacuum dried to obtain a compatibilizer; wherein the mass ratio of polyethylene grafted acrylic acid to polyurethane prepolymer is 100:8; Step 3: S31: Disperse 3-amino-1,2,4-triazole and hydroxycitronellal in anhydrous ethanol, heat and reflux for 8 hours, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and continue to reflux for 8 hours, cool naturally after the reaction is completed, wash the precipitate by centrifugation with anhydrous ethanol, and vacuum dry to obtain a flame retardant; wherein the molar ratio of 3-amino-1,2,4-triazole, hydroxycitronellal and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1:1; S32: 100 kg of polyurethane prepolymer and 14 kg of dihydroxy-terminated polydimethylsiloxane were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 70°C under nitrogen protection, the temperature was kept for reaction for 2 hours, 2.5 kg of 1,4-butanediol was added, and the chain extension reaction was performed for 1 hour; 10 kg of flame retardant was continuously added, the end-capping reaction was performed for 0.5 hours, and the silicon-containing flame-retardant polyurethane was obtained by aging; Step 4: 85% high-density polyethylene and 15% silicon-containing flame-retardant polyurethane are mixed by weight to obtain a mixed material; 100 kg of the mixed material, 12 kg of a compatibilizer, 8 kg of carbon nanotubes, 4.5 kg of light calcium carbonate and 2.8 kg of an antioxidant are melted and stirred at 200 ° C, cooled to 110 ° C, 1 kg of diisopropylbenzene peroxide is added for cross-linking reaction for 120 seconds, and the finished product is obtained through injection molding, demolding, trimming, cutting, edge sealing and polishing.

[0020] Embodiment 2: A high-strength belt for a range hood that is resistant to fracture and a method for preparing the same, comprising the following steps: Step 1: Toluene diisocyanate and polypropylene glycol 1000 are mixed, a catalyst dibutyltin dilaurate is added, and the mixture is stirred and reacted at 80° C. under nitrogen protection to obtain a polyurethane prepolymer; wherein the toluene diisocyanate and polypropylene glycol 1000 are reacted in a molar ratio of 2:1; Step 2: S21: mixing low-density polyethylene and xylene, heating until the polyethylene is dissolved, adding acrylic acid and benzoyl peroxide to react, pouring the product into anhydrous ethanol, filtering out the mother liquor, soaking the precipitate in anhydrous ethanol for washing, and vacuum drying to obtain polyethylene grafted with acrylic acid; wherein the weight ratio of benzoyl peroxide, acrylic acid and polyethylene is 0.5:15:100; S22: polyethylene grafted acrylic acid and polyurethane prepolymer are mixed, heated to 95°C under nitrogen environment, reacted for 11 hours, cooled to 65°C, unreacted isocyanate groups are capped with anhydrous ethanol, ungrafted polyurethane prepolymer in the reactants is removed with N,N-dimethylformamide, and vacuum dried to obtain a compatibilizer; wherein the mass ratio of polyethylene grafted acrylic acid to polyurethane prepolymer is 100:8; Step 3: S31: Disperse 3-amino-1,2,4-triazole and hydroxycitronellal in anhydrous ethanol, heat and reflux for 9 hours, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and continue to reflux for 8.5 hours, cool naturally after the reaction is completed, wash the precipitate by centrifugation with anhydrous ethanol, and vacuum dry to obtain a flame retardant; wherein the molar ratio of 3-amino-1,2,4-triazole, hydroxycitronellal and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1:1; S32: 100 kg of polyurethane prepolymer and 14 kg of dihydroxy-terminated polydimethylsiloxane were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 80°C under nitrogen protection, the temperature was kept for reaction for 2.5 hours, 2.5 kg of 1,4-butanediol was added, and the chain extension reaction was performed for 1.5 hours; 10 kg of flame retardant was continuously added, the end-capping reaction was performed for 0.5 hours, and the silicon-containing flame-retardant polyurethane was obtained by aging; Step 4: 88% high-density polyethylene and 12% silicon-containing flame-retardant polyurethane are mixed by weight to obtain a mixed material; 100 kg of the mixed material, 12 kg of a compatibilizer, 8 kg of carbon nanotubes, 4.5 kg of light calcium carbonate and 2.8 kg of an antioxidant are melted and stirred at 210°C, cooled to 115°C, 1 kg of diisopropylbenzene peroxide is added for cross-linking reaction for 125 seconds, and a finished product is obtained through injection molding, demolding, trimming, cutting, edge sealing and polishing.

[0021] Embodiment 3: A high-strength belt for a range hood that is resistant to fracture and a method for preparing the same, comprising the following steps: Step 1: Toluene diisocyanate and polypropylene glycol 1000 are mixed, a catalyst dibutyltin dilaurate is added, and the mixture is stirred and reacted at 90° C. under nitrogen protection to obtain a polyurethane prepolymer; wherein the toluene diisocyanate and polypropylene glycol 1000 are reacted in a molar ratio of 2:1; Step 2: S21: mixing low-density polyethylene and xylene, heating until the polyethylene is dissolved, adding acrylic acid and benzoyl peroxide to react, pouring the product into anhydrous ethanol, filtering out the mother liquor, soaking the precipitate in anhydrous ethanol for washing, and vacuum drying to obtain polyethylene grafted with acrylic acid; wherein the weight ratio of benzoyl peroxide, acrylic acid and polyethylene is 0.5:15:100; S22: polyethylene grafted acrylic acid and polyurethane prepolymer are mixed, heated to 100°C under nitrogen environment, reacted for 12 hours, cooled to 70°C, unreacted isocyanate groups are capped with anhydrous ethanol, ungrafted polyurethane prepolymer in the reactants is removed with N,N-dimethylformamide, and vacuum dried to obtain a compatibilizer; wherein the mass ratio of polyethylene grafted acrylic acid to polyurethane prepolymer is 100:8; Step 3: S31: Disperse 3-amino-1,2,4-triazole and hydroxycitronellal in anhydrous ethanol, heat and reflux for 10 hours, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and continue to reflux for 9 hours, cool naturally after the reaction is completed, wash the precipitate by centrifugation with anhydrous ethanol, and vacuum dry to obtain a flame retardant; wherein the molar ratio of 3-amino-1,2,4-triazole, hydroxycitronellal and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1:1; S32: 100 kg of polyurethane prepolymer and 14 kg of dihydroxy-terminated polydimethylsiloxane were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 90°C under nitrogen protection, the temperature was kept for reaction for 3 hours, 2.5 kg of 1,4-butanediol was added, and the chain extension reaction was carried out for 2 hours; 10 kg of flame retardant was further added, the end-capping reaction was carried out for 1 hour, and the silicon-containing flame-retardant polyurethane was obtained by aging; Step 4: 90% high-density polyethylene and 10% silicon-containing flame-retardant polyurethane are mixed by weight to obtain a mixed material; 100kg of the mixed material, 12kg of a compatibilizer, 8kg of carbon nanotubes, 4.5kg of light calcium carbonate and 2.8kg of an antioxidant are melted and stirred at 230°C, cooled to 120°C, 1kg of diisopropylbenzene peroxide is added and cross-linked for 130s, and a finished product is obtained through injection molding, demolding, trimming, cutting, edge sealing and polishing.

[0022] Comparative Example 1: No compatibilizer was added, and other parameters were the same as those in Example 1.

[0023] Step 1: Toluene diisocyanate and polypropylene glycol 1000 are mixed, a catalyst dibutyltin dilaurate is added, and the mixture is stirred and reacted at 75° C. under nitrogen protection to obtain a polyurethane prepolymer; wherein the toluene diisocyanate and polypropylene glycol 1000 are reacted in a molar ratio of 2:1; Step 2: S21: Disperse 3-amino-1,2,4-triazole and hydroxycitronellal in anhydrous ethanol, heat and reflux for 8 hours, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and continue to reflux for 8 hours, cool naturally after the reaction is completed, wash the precipitate by centrifugation with anhydrous ethanol, and vacuum dry to obtain a flame retardant; wherein the molar ratio of 3-amino-1,2,4-triazole, hydroxycitronellal and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1:1; S22: 100 kg of polyurethane prepolymer and 14 kg of dihydroxy-terminated polydimethylsiloxane were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 70°C under nitrogen protection, the temperature was kept for reaction for 2 hours, 2.5 kg of 1,4-butanediol was added, and the chain extension reaction was performed for 1 hour; 10 kg of flame retardant was further added, the end-capping reaction was performed for 0.5 hours, and the silicon-containing flame-retardant polyurethane was obtained by aging; Step 3: 85% high-density polyethylene and 15% silicon-containing flame-retardant polyurethane are mixed by weight to obtain a mixed material; 100 kg of the mixed material, 12 kg of a compatibilizer, 8 kg of carbon nanotubes, 4.5 kg of light calcium carbonate and 2.8 kg of an antioxidant are melted and stirred at 200 ° C, cooled to 110 ° C, 1 kg of diisopropylbenzene peroxide is added for cross-linking reaction for 120 seconds, and the finished product is obtained through injection molding, demolding, trimming, cutting, edge sealing and polishing.

[0024] Comparative Example 2: conventional polyurethane was used instead of the silicon-containing flame-retardant polyurethane, and the other parameters were the same as those in Example 2.

[0025] Step 1: Toluene diisocyanate and polypropylene glycol 1000 are mixed, a catalyst dibutyltin dilaurate is added, and the mixture is stirred and reacted at 80° C. under nitrogen protection to obtain a polyurethane prepolymer; wherein the toluene diisocyanate and polypropylene glycol 1000 are reacted in a molar ratio of 2:1; Step 2: S21: mixing low-density polyethylene and xylene, heating until the polyethylene is dissolved, adding acrylic acid and benzoyl peroxide to react, pouring the product into anhydrous ethanol, filtering out the mother liquor, soaking the precipitate in anhydrous ethanol for washing, and vacuum drying to obtain polyethylene grafted with acrylic acid; wherein the weight ratio of benzoyl peroxide, acrylic acid and polyethylene is 0.5:15:100; S22: polyethylene grafted acrylic acid and polyurethane prepolymer are mixed, heated to 95°C under nitrogen environment, reacted for 11 hours, cooled to 65°C, unreacted isocyanate groups are capped with anhydrous ethanol, ungrafted polyurethane prepolymer in the reactants is removed with N,N-dimethylformamide, and vacuum dried to obtain a compatibilizer; wherein the mass ratio of polyethylene grafted acrylic acid to polyurethane prepolymer is 100:8; Step 3: Using dibutyltin dilaurate as a catalyst, 100 kg of polyurethane prepolymer and 8.6 kg of 1,4-butanediol were mixed under nitrogen protection at 80°C, and the chain extension reaction was carried out for 1.5 hours; 10 kg of ethanol was added to cap the reaction for 0.5 hours, and the silicon-containing flame-retardant polyurethane was obtained by aging; Step 4: 88% high-density polyethylene and 12% silicon-containing flame-retardant polyurethane are mixed by weight to obtain a mixed material; 100 kg of the mixed material, 12 kg of a compatibilizer, 8 kg of carbon nanotubes, 4.5 kg of light calcium carbonate and 2.8 kg of an antioxidant are melted and stirred at 210°C, cooled to 115°C, 1 kg of diisopropylbenzene peroxide is added for cross-linking reaction for 125 seconds, and a finished product is obtained through injection molding, demolding, trimming, cutting, edge sealing and polishing.

[0026] Comparative Example 3: The amount of silicon-containing flame-retardant polyurethane was increased, and the other parameters were the same as those in Example 3.

[0027] Step 1: Toluene diisocyanate and polypropylene glycol 1000 are mixed, a catalyst dibutyltin dilaurate is added, and the mixture is stirred and reacted at 90° C. under nitrogen protection to obtain a polyurethane prepolymer; wherein the toluene diisocyanate and polypropylene glycol 1000 are reacted in a molar ratio of 2:1; Step 2: S21: mixing low-density polyethylene and xylene, heating until the polyethylene is dissolved, adding acrylic acid and benzoyl peroxide to react, pouring the product into anhydrous ethanol, filtering out the mother liquor, soaking the precipitate in anhydrous ethanol for washing, and vacuum drying to obtain polyethylene grafted with acrylic acid; wherein the weight ratio of benzoyl peroxide, acrylic acid and polyethylene is 0.5:15:100; S22: polyethylene grafted acrylic acid and polyurethane prepolymer are mixed, heated to 100°C under nitrogen environment, reacted for 12 hours, cooled to 70°C, unreacted isocyanate groups are capped with anhydrous ethanol, ungrafted polyurethane prepolymer in the reactants is removed with N,N-dimethylformamide, and vacuum dried to obtain a compatibilizer; wherein the mass ratio of polyethylene grafted acrylic acid to polyurethane prepolymer is 100:8; Step 3: S31: Disperse 3-amino-1,2,4-triazole and hydroxycitronellal in anhydrous ethanol, heat and reflux for 10 hours, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and continue to reflux for 9 hours, cool naturally after the reaction is completed, wash the precipitate by centrifugation with anhydrous ethanol, and vacuum dry to obtain a flame retardant; wherein the molar ratio of 3-amino-1,2,4-triazole, hydroxycitronellal and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1:1; S32: 100 kg of polyurethane prepolymer and 14 kg of dihydroxy-terminated polydimethylsiloxane were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 90°C under nitrogen protection, the temperature was kept for reaction for 3 hours, 2.5 kg of 1,4-butanediol was added, and the chain extension reaction was carried out for 2 hours; 10 kg of flame retardant was further added, the end-capping reaction was carried out for 1 hour, and the silicon-containing flame-retardant polyurethane was obtained by aging; Step 4: 80% high-density polyethylene and 20% silicon-containing flame-retardant polyurethane are mixed by weight to obtain a mixed material; 100kg of the mixed material, 12kg of a compatibilizer, 8kg of carbon nanotubes, 4.5kg of light calcium carbonate and 2.8kg of an antioxidant are melt-stirred at 230°C, cooled to 120°C, 1kg of diisopropylbenzene peroxide is added and cross-linked for 130s, and a finished product is obtained through injection molding, demolding, trimming, cutting, edge sealing and polishing.

[0028] Experiment: The performance of the belts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested.

[0029] Flame retardant properties: Test limiting oxygen index.

[0030] Tensile strength: The test was carried out in accordance with the standard GB / T1040-2006. The sample was dumbbell-shaped, the tensile rate was 50 mm / min, the gauge length was 25 mm, and the tensile strength and elongation at break were tested.

[0031] Friction coefficient: The test was carried out using a friction coefficient / peel tester (FPT-F1, Jinan Labthink Electromechanical Technology Co., Ltd.).

[0032] The experimental results are shown in Table 1.

[0033] Table 1. Test results of various performances of special belts for range hoods

[0034] Conclusion: The data of Examples 1 to 3 and Comparative Examples 1 to 3 show that the special belt for range hoods prepared by the present invention has good performance. The data of Example and Comparative Example 1 show that the compatibilizer improves the compatibility between polyethylene and silicon-containing flame-retardant polyurethane, thereby improving the performance of the product. The data of Example 2 and Comparative Example 2 show that compared with conventional polyurethane, silicon-containing flame-retardant polyurethane improves flame retardancy, reduces friction coefficient, and improves wear resistance. The data of Example 3 and Comparative Example 3 show that increasing the amount of silicon-containing flame-retardant polyurethane reduces the mechanical properties and friction coefficient of the product.

[0035] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-strength belt for a range hood that is resistant to breakage, characterized in that: The following steps are involved: High-density polyethylene and silicon-containing flame-retardant polyurethane are mixed to obtain a mixed material; the mixed material, a compatibilizer, carbon nanotubes, light calcium carbonate, and an antioxidant are melted and stirred at 200-230° C., the temperature is lowered to 110-120° C., dicumyl peroxide is added for cross-linking reaction for 120-130 seconds, and a finished product is obtained through injection molding, demolding, trimming, cutting, edge sealing, and polishing.

2. The method for preparing a high-strength anti-fracture belt for a range hood according to claim 1, characterized in that: In the mixed material, the content of each component, by weight, is 85-90% high-density polyethylene and 10-15% silicon-containing flame-retardant polyurethane.

3. The method for preparing a high-strength anti-fracture belt for a range hood according to claim 1, characterized in that: Calculated by weight, the amount of each component is: 100 parts of mixed material, 8 to 12 parts of compatibilizer, 5 to 9 parts of carbon nanotubes, 3 to 5 parts of light calcium carbonate, and 2 to 3 parts of antioxidant.

4. The method for preparing a high-strength anti-fracture belt for a range hood according to claim 1, characterized in that: The preparation method of the compatibilizer comprises the following steps: Step 1: Toluene diisocyanate and polypropylene glycol 1000 are mixed, dibutyltin dilaurate as a catalyst is added, and the mixture is stirred and reacted at 75-90°C under nitrogen protection to obtain a polyurethane prepolymer; Step 2: Mix low-density polyethylene and xylene, heat until the polyethylene is dissolved, add acrylic acid and benzoyl peroxide to react, pour the product into anhydrous ethanol, filter out the mother liquor, soak the precipitate in anhydrous ethanol for washing, and vacuum dry to obtain polyethylene grafted with acrylic acid; Step 3: The polyethylene grafted acrylic acid and the polyurethane prepolymer are mixed, and the temperature is raised to 90-100°C under the protection of a nitrogen environment. After reacting for 10-12 hours, the temperature is lowered to 60-70°C, and the unreacted isocyanate groups are capped with anhydrous ethanol. The ungrafted polyurethane prepolymer in the reactant is removed with N,N-dimethylformamide, and vacuum dried to obtain a compatibilizer.

5. The method for preparing a high-strength anti-fracture belt for a range hood according to claim 4, characterized in that: In step 1, toluene diisocyanate and polypropylene glycol 1000 are reacted at a molar ratio of 2:

1.

6. The method for preparing a high-strength anti-fracture belt for a range hood according to claim 4, characterized in that: In step 2, the weight ratio of benzoyl peroxide, acrylic acid and polyethylene is (0.5-0.8):(12-15):

100.

7. The method for preparing a high-strength anti-fracture belt for a range hood according to claim 4, characterized in that: In step 3, the mass ratio of polyethylene grafted acrylic acid to polyurethane prepolymer is 100:(8~10).

8. The method for preparing a high-strength anti-fracture belt for a range hood according to claim 1, characterized in that: The method for preparing silicon-containing flame-retardant polyurethane comprises the following steps: S1: Toluene diisocyanate and polypropylene glycol 1000 are mixed, dibutyltin dilaurate as a catalyst is added, and the mixture is stirred and reacted at 75-90° C. under nitrogen protection to obtain a polyurethane prepolymer; S2: Disperse 3-amino-1,2,4-triazole and hydroxycitronellal in anhydrous ethanol, heat and reflux for 8-10 hours, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and continue to reflux for 8-9 hours, cool naturally after the reaction is completed, wash the precipitate with anhydrous ethanol by centrifugation, and vacuum dry to obtain a flame retardant; S3: Mix the polyurethane prepolymer and dihydroxy-terminated polydimethylsiloxane, use dibutyltin dilaurate as a catalyst, raise the temperature to 70-90°C under nitrogen protection, keep the temperature for reaction for 2-3 hours, add 1,4-butanediol, and extend the chain for 1-2 hours; continue to add flame retardant, capping reaction for 0.5-1 hour, and mature to obtain silicon-containing flame-retardant polyurethane.

9. The method for preparing a high-strength anti-fracture belt for a range hood according to claim 8, characterized in that: In S1, toluene diisocyanate and polypropylene glycol 1000 are reacted in a molar ratio of 2:1; In S2, the molar ratio of 3-amino-1,2,4-triazole, hydroxycitronellal, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1:1; In S3, the amount of each component, by weight, is 100 parts of polyurethane prepolymer, 10-15 parts of dihydroxy-terminated polydimethylsiloxane, 2-3 parts of 1,4-butanediol, and 8-10 parts of flame retardant.

10. A special belt for range hoods which is anti-fracture and high in strength and is prepared according to the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Low-energy-consumption, high-flame-retardancy, low-smoke and halogen-free cable material

    CN105199187A

  • Wear-resistant high-temperature-resistant conveyor belt and production method

    CN110305385A

  • Epoxy resin-based flame-retardant circuit board and preparation method thereof

    CN115802597A

  • Flame-retardant regenerated plastic and preparation method thereof

    CN117384443A

  • Process for the preparation of 9,10-dihydro-9-oxa-10-organyl-oxyphosphaphenanthren-10-oxide or thiono and derivatives of the same substituted on the phenyl groups

    EP1506968A1

Cited By

  • PVC automobile film and preparation method thereof

    CN121182098A